Expression of Genes Associated with the Growth of Symbiotically Grown Dendrobium bigibbum Lindl. - VALENTINO, MARY JHANE; Sotto, R. C.; Dionisio-Sese, M. L.; Lantican, N. B.; Bautista, N. S.2 (International Journal of Agricultural Technology, 2025)
The study evaluated the expression of genes related to the growth of symbiotically grown Dendrobium bigibbum were evaluated (biosynthesis/ signal transduction of auxin and gibberellins, common symbiotic pathway, and mycorrhizal-induced putative genes). Results revealed that the relative expression of genes were upregulated in D. bigibbum co-cultured with Volvariella volvacea. Meanwhile, in Lentinus tigrinus, DOSAUR71(seedling stage) was downregulated and the cycle treshhold value for DoSWEET14 was unchanged. In D. bigibbum co-cultured with Pleurotus florida, downregulation of GA3ox (seedling stage), DOSAUR71 (rhizoid and seedling stages) and DoIPM (rhizoid stage) were observed and unchanged relative gene expressions of DoIPM (seedling stage) and DoSWEET14 (seedling stage) were recorded. Thus, both V. volvacea and L. tigrinus formed compatible mycorrhizal association with D. bigibbum which caused increase in the growth of D. bigibbum during rhizoid and seedling stages.